MODEL PEMBELAJARAN BERBASIS TPACK DALAM MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MAPEL PAI DAN BP DI SMAN 1 KINALI - Suharjo Suharjo; Alizar Alizar; Andi Peta Wahyu Cahyono (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This study is entitled TPACK-Based Learning Model in Improving Students' Understanding of Islamic Religious Education Subjects at SMAN 1 Kinali. This study aims to evaluate the effectiveness of the application of the TPACK (Technological Pedagogical Content Knowledge) model in Islamic Religious Education (PAI) learning at SMAN 1 Kinali. The TPACK model integrates technology, pedagogy, and content knowledge to improve students' understanding of teaching materials while honing digital literacy skills. This study uses the Classroom Action Research (CAR) method which is implemented in three cycles, with stages of planning, action, observation, and reflection. The subjects of the study were grade XI students who studied the material "Avoiding Teenage Fights, Alcohol, and Drugs". The results showed that the TPACK learning model succeeded in improving students' understanding of Islamic Religious Education material, as well as improving spiritual, social attitudes, and psychomotor skills. In addition, students also showed a significant increase in digital literacy skills through the use of technology integrated into learning. Overall, this study concludes that the TPACK learning model is effective in improving the quality of Islamic Religious Education learning, especially in terms of students' understanding of Islamic teachings and their digital skills. Thus, the implementation of TPACK at SMAN 1 Kinali can be used as a relevant and applicable learning model in today's digital era.